2018
DOI: 10.4103/0973-1482.187239
|View full text |Cite
|
Sign up to set email alerts
|

Poorly differentiated carcinoma of thyroid

Abstract: Malignant thyroid tumors of follicular origin comprise a spectrum, with the indolent well-differentiated thyroid carcinoma (WDTC) at one end and lethal anaplastic thyroid carcinoma (ATC) at the other. Poorly differentiated thyroid carcinoma (PDTC) lies intermediately between WDTC and ATC in terms of morphology and prognostic standpoint. This thyroglobulin producing neoplasm accounts for 4-7% of all thyroid malignancies. PDTC has been controversial due to lack of defined diagnostic criteria. We hereby report a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In the majority of studies in our review, the extent of the poorly differentiated area was not reported, and a PDTC definition was decided to address this component. A large number of patients with PDTC reviewed herein presented with locally advanced disease (T3 or T4, extrathyroidal extension, and nodal involvement) [ 40 , 44 , 46 , 47 , 49 , 50 , 51 , 54 , 55 , 57 , 58 , 60 , 61 , 62 , 64 , 67 , 68 , 69 , 70 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 90 , 91 , 92 , 94 , 97 , 98 , 99 , 100 , 101 , 102 , 107 , 108 , 109 , 111 , 112 , 113 , 114 , 115 , 116 ,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of studies in our review, the extent of the poorly differentiated area was not reported, and a PDTC definition was decided to address this component. A large number of patients with PDTC reviewed herein presented with locally advanced disease (T3 or T4, extrathyroidal extension, and nodal involvement) [ 40 , 44 , 46 , 47 , 49 , 50 , 51 , 54 , 55 , 57 , 58 , 60 , 61 , 62 , 64 , 67 , 68 , 69 , 70 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 90 , 91 , 92 , 94 , 97 , 98 , 99 , 100 , 101 , 102 , 107 , 108 , 109 , 111 , 112 , 113 , 114 , 115 , 116 ,…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of studies in our review, the extent of the poorly differentiated area was not reported, and a PDTC definition was decided to address this component. A large number of patients with PDTC reviewed herein presented with locally advanced disease (T3 or T4, extrathyroidal extension, and nodal involvement) [40,44,46,47,[49][50][51]54,55,57,58,[60][61][62]64,[67][68][69][70][71][73][74][75][76][77][78][80][81][82][83][84][85][86][87][88][90][91][92]94,[97][98][99][100][101][102][107][108][109]…”
Section: Histologymentioning
confidence: 99%
“…PDTCs represents about 0.3% to 6.7% of all thyroid malignancies and display an aggressive clinical behavior, with a poor prognosis [8]. Anaplastic thyroid cancer (ATC) is the most aggressive and lethal form of UDTCs.…”
Section: Introductionmentioning
confidence: 99%